PENGARUH STRATEGI PEMBELAJARAN GENERATIF BERBANTUAN AUDIO-VISUALTERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Panjaitan, Jelita; Nababan, Tuti (LPPM Universitas Darma Agung, 2020)
This study aims at determining the significant effect of audio-visual assisted generative learning strategies on students' critical thinking skills in the Measurement Material for class X Semester I SMA Nurani Belawan T.P 2019/2020. The population in this study is all class X students of Nurani Belawan Private High School which consists of 4 classes totaling 120 students. The research sample was taken from 2 classes with cluster random sampling, so class X-2 was chosen as the experimental class which was taught using generative learning strategies assisted by audio-visual and class X-4 as the control class which was taught using the direct learning model. Each class consists of 30 students. The instrument in this study consists of 9 items in the form of essays that has been tested for validity, reliability, difficulty level, and distinction. The results show that the sample coming from a homogeneous population and normal distribution. The results show that the pre-test average value for the audio-visual assisted generative learning strategy is 35.28 and the direct learning class is 35.21. From the results of the two-party t test, it was obtained tcount = 0.248 ttable = 2.002 because tcount < ttable , it can be concluded that the initial abilities of the two classes are the same. A different treatment were given and post-test was given.After the posttest was carried out, the post-test average score for the generative audio-visual assisted learning strategy is 82.42 and the post-test average score for direct learning is 68.57. The results of the t-test for one party obtained tcount = 9.964 and ttable = 1.671 because tcount > ttable, this shows that there is a significant effect of Audio-Visuala Assisted Generative Learning Strategies on Students' Critical Thinking Ability on Measurement Materials in class X Nurani Belawan Private Senior High School Academic Year 2019 / 2020.